2017
DOI: 10.1038/leu.2017.193
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of CSF1R-blocking antibodies in multiple myeloma

Abstract: Our previous studies showed that macrophages (MФs), especially myeloma-associated MФs (MAMs) induce chemoresistance in human myeloma. Here we explored the potential of targeting MФs, by using colony-stimulating factor 1 receptor (CSF1R)-blocking mAbs, to treat myeloma. Our results showed that CSF1R blockade specifically inhibited the differentiation, proliferation and survival of murine M2 MФs and MAMs, and repolarized MAMs towards M1-like MФs in vitro. CSF1R blockade alone inhibited myeloma growth in vivo, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 44 publications
3
66
0
1
Order By: Relevance
“…A similar effect was recently observed in AML where CSF1R inhibition reduced paracrine growth signals from the TME, resulting in reduced leukemic cell viability [76]. In MM, blocking CSF1R with antibody or depleting macrophages both led to reduced tumor growth and sensitized myeloma cells to chemotherapy in vivo [77]. The antitumoral effects of CSF1 blockade was also observed in mantle cell lymphoma where treatments with GW2580, a CSF1R inhibitor reduced lymphoma cell survival, irrespective of their sensitivity to ibrutinib, a Bruton's tyrosine kinase (BTK) inhibitor [78].…”
Section: New Macrophage-targeting Therapies In Hematologic Malignanciessupporting
confidence: 58%
“…A similar effect was recently observed in AML where CSF1R inhibition reduced paracrine growth signals from the TME, resulting in reduced leukemic cell viability [76]. In MM, blocking CSF1R with antibody or depleting macrophages both led to reduced tumor growth and sensitized myeloma cells to chemotherapy in vivo [77]. The antitumoral effects of CSF1 blockade was also observed in mantle cell lymphoma where treatments with GW2580, a CSF1R inhibitor reduced lymphoma cell survival, irrespective of their sensitivity to ibrutinib, a Bruton's tyrosine kinase (BTK) inhibitor [78].…”
Section: New Macrophage-targeting Therapies In Hematologic Malignanciessupporting
confidence: 58%
“…A recent study reported that CSF‐1R inhibitors exhibited anti‐tumour activity in AML by blocking paracrine signals from support cells 21 . Moreover, the effect of CSF‐1R inhibitors has been also shown in multiple myeloma and in CLL 19,22 . BLZ945 is a CSF‐1R inhibitor that selectively binds to CSF‐1R expressed on TAMs and inhibits the proliferation of TAMs 32‐34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CSF‐1R blockage by inhibitors or antibodies improves the efficacy of chemotherapy in multiple solid tumours, such as glioma, cervical and mammary tumour 17,18 . Furthermore, targeting CSF‐1R has been proven effective on haematopoietic malignancies, such as multiple myeloma, chronic lymphocytic leukaemia (CLL) and a subset of AML 19‐23 …”
Section: Introductionmentioning
confidence: 99%
“…In summary, we hypothesize that the observed in vitro and in ovo regulation of CD206 in Mφ might also occur in vivo and contribute to CD206 abundance in advanced stages of HL. Our data identify CD206 as a potential target for the modulation of Mφ activation in addition to the recently discussed targeting of the CSF1R (Luo et al, 2006;Mart ın-Moreno et al, 2015;Pham et al, 2018;Pyonteck et al, 2013;Ries et al, 2014;Wang et al, 2018;Zhu et al, 2014). Inhibition of the Jak/STAT pathway targets not only lymphoma cells directly, but may also affect lymphoma-educated Mφ development and/or activity.…”
Section: Discussionmentioning
confidence: 70%